KEEFEKTIFAN PENGGUNAAN METODE DRILL BERSTRATEGI QUESTIONS STUDENTS HAVE TERHADAP HASIL BELAJAR STOIKIOMETRI - Pamenang, Fransisca Ditawati Nur; Soeprodjo, Soeprodjo (Chemistry in Education, 2019)
The purpose of this research to determine the effectiveness of the use of the drill method using Questions Students Have strategy to the stoichiometry learning outcomes of chemistry at SMA N 1 Muntilan. The design used in this research is pre-test and post-test group design. Sampling was done by cluster random sampling technique, and obtained grade X MS-1 as a control group and grade X MS-3 as a experimental group. Data collecting used some methods as documentations, tests, observation, and questionnaires. The test is used to analyze the data is the estimated average test results of cognitive learning and mastery learning classical test. Test results obtained by the proportion of cognitive mastery learning classical was 26 of 30 students achieving minimum completeness criteria for experimental group, and only 18 of 30 students in the control group achieving minimum completeness criteria. Research result shown the average estimate in the experimental group was 79,7 to 85,9 and control group was between 72,8 to 80,8. The results of the data analysis it can be concluded that the use of drill method using Questions Students Have strategy provide effectiveness on students learning outcomes of chemistry.Â